Pancreatitis - Victorovich Garbuzenko, Dmitry (IntechOpen, 2019)
The book "Pancreatitis" is devoted to the actual and, in some cases, controversial and unresolved problems associated with acute and chronic pancreatitis. The material presented in it will be of interest to anyone who considers pancreatology their specialty.